Physicochemical, microbiological and biological properties of fermented kepayang (Pangium edule Reinw.) seeds - Mustaffer, Nur Hafizah (2020)
Kepayang (Pangium edule Reinw.) is one of the indigenous fruits in Malaysia, Indonesia, Papua New Guinea, Vanuatu, and the Philippines. This P. edule Reinw. seeds can be developed as a functional food through fermentation. Unfortunately, the properties of fermented P. edule Reinw. seeds are not well reported yet. Therefore, the aims of this study were to analyse the physicochemical and microbiological characteristics of P. edule Reinw. seeds during fermentation process. Besides that, the objective of this study was to determine the antimicrobial and antioxidant activities of P. edule Reinw. seeds extract and to identify the presence of bioactive compounds in raw and fermented P. edule Reinw. seeds extract. These P. edule Reinw. seeds were obtained from Jerantut, Pahang in July 2018. These P. edule Reinw. seeds were undergone the spontaneous fermentation process which covered with charcoal for 40 days. The physicochemical properties were evaluated according to the Association of Analytical Communities (AOAC) methods while the microbiological analysis was determined using microbial selective media. Then, the raw and fermented P. edule Reinw. seeds were extracted using ethanol and water. The antimicrobial activity was following the Clinical and Laboratory Standard Institute (CLSI) methods. The antioxidant activity was measured using 2,2- diphenyl-1-dipicrylhydrazyl (DPPH) radical scavenging assay while total phenolic content was measured by following Folin-Ciocalteu methods. Other than that, the bioactive compounds present in extracts were identified using gas chromatography-mass spectrometry (GC-MS) profile and liquid chromatography-mass spectrometry (LC-MS) profile. In this study, the results showed that there were no significant differences in water activity while the pH value was decreased along fermentation days. The TSS was significantly increased from day 0 (11.00) to day 30 (19.50), however, it drastically decreased after 40 days fermentation which is 11.50. The value of lightness (L*) parameter was decreased from 66.44 on day 0 to 25.28 on day 40. There were no significant differences for a* and b* parameter. For proximate analysis, the percentage of ash, crude protein, crude fat, and crude fibre were significantly increased while moisture content and carbohydrate were significantly decreased along the fermentation day. The microbiological analysis showed the reducing number of B. cereus from 2.15 Log10 CFU/g to not detected on day 40, while there were slightly increase in the number of TPC, coliform, mould and yeast, S. aureus, P. aeruginosa and LAB. Interestingly, there was no Salmonella spp. and E. coli detected along fermentation process. The antimicrobial activity of raw and fermented seeds extract was evaluated against 16 types of pathogenic microorganisms. The disc diffusion assay (DDA) showed that the microorganisms were inhibited by extracts in the range of 6.25 mm and 9.88 mm. The lowest MIC and MBC values were at concentration 6.25 mg/mL and 12.50 mg/mL extract, respectively. Generally, the time-kill curve study showed that B. cereus, K. pneumoniae, P. aeruginosa, S. aureus, and C. albicans can be killed using raw and fermented P. edule Reinw. seeds extract. Besides, the highest DPPH activity was observed in ferment-water extract at concentration 10 mg/mL which about 95.61% while the highest total phenolic content was obtained from the ferment-ethanol extract (173.79 mg GAE/100 mg). The GC-MS analysis revealed the volatile compounds in raw and fermented P. edule Reinw. seeds extract while LC-MS analysis was used to identify the non-volatile compounds in both positive and negative ion modes. In conclusion, there were some changes in the physicochemical properties of P. edule Reinw. seeds during fermentation, nonetheless, the fermented seeds showed a low level of microbial counts and potentially has the antimicrobial and antioxidant activities. The results of this study might be used as basic information to develop the fermented seeds as a functional food.